Early onset cerebral infarction in Schimke immuno-osseous dysplasia: A case report - Babaei, Amir Hossein; Inaloo, Soroor; Basiratnia, Mitra; Derakhshan, Ali (Iranian Journal of Child Neurology, 2018)
Schimke Immuno-Osseous Dysplasia is a rare autosomal recessive disease caused by a biallelic mutation in SMARCAL1 gene. Typical findings in Schimke Immuno-Osseous Dysplasia include spondylo-epiphyseal dysplasia, steroid resistance nephrotic syndrome, progressive renal failure, T-cell immunodeficiency, bone marrow failure, and cerebral infarction. In this case report, we described a 9-year-old girl who presented with failure to thrive in infancy. Nephrotic syndrome was diagnosed at the age of four years. She had three episodes of admission with cerebral stroke due to moyamoya syndrome. In the last admission, she had new cerebral ischemia, developed seizure, and finally died.